2011
DOI: 10.1128/jvi.00657-10
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Configuration of Hepatitis E Virus Antigenic Domain

Abstract: Hepatitis E virus (HEV) is a human pathogen that causes acute hepatitis. When an HEV capsid protein containing a 52-amino-acid deletion at the C terminus and a 111-amino-acid deletion at the N terminus is expressed in insect cells, the recombinant HEV capsid protein can self-assemble into a T‫1؍‬ virus-like particle (VLP) that retains the antigenicity of the native HEV virion. In this study, we used cryoelectron microscopy and image reconstruction to show that anti-HEV monoclonal antibodies bind to the protrud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
99
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 31 publications
0
99
2
1
Order By: Relevance
“…Meanwhile, this residue was also reported to be one of the several essential residues for host cell interaction [9]. To have a better spatial view of all the key epitope sites, i.e., the potential receptor binding sites, we mapped all the residues that have been shown to be involved in binding to the host cell ( Figure 7, Table 2 and Supplementary information, Figure S11) on the surface of T = 3 virion-sized particle [31] ( Figure 7A) and T = 1 HEV VLP [9,10,32] (Figure 7B). Interestingly all of these residues within E2 domain are located either in the dimerization region or in the groove region.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, this residue was also reported to be one of the several essential residues for host cell interaction [9]. To have a better spatial view of all the key epitope sites, i.e., the potential receptor binding sites, we mapped all the residues that have been shown to be involved in binding to the host cell ( Figure 7, Table 2 and Supplementary information, Figure S11) on the surface of T = 3 virion-sized particle [31] ( Figure 7A) and T = 1 HEV VLP [9,10,32] (Figure 7B). Interestingly all of these residues within E2 domain are located either in the dimerization region or in the groove region.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic deletions or cellular processing resulting in the loss of the N-terminal 111 or 13 amino acids (aa) or of the C-terminal 52 aa (C52aa) yielded capsid protein capable of directing the formation of the HEV small (S) or large (L) VLPs (3)(4)(5). Particle formation was required for C52aa abbreviation, limiting the structural analysis of the resulting particles (3,4,(6)(7)(8)(9)(10). However, the contribution of the C52aa-encoding sequence was confirmed by both in vivo (attenuated infectivity of the point mutant virus in nonhuman primates) and in vitro (reduced RNA synthesis by RNA-dependent RNA polymerase [RdRp]) assays (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…The infection is lifethreatening during pregnancy, causing fatal and fulminant hepatitis with a high rate of miscarriage and premature birth [7]. Epidemiological studies have reported a mortality rate of up to 30% in pregnant women [7].…”
Section: Introductionmentioning
confidence: 99%
“…According to the phylogenetic analysis, HEV has 5 genotypes with different geographical distributions and hosts [7]. Humans may cause serious consequences in pregnant women and patients with chronic liver disease [2,7]. The infection is lifethreatening during pregnancy, causing fatal and fulminant hepatitis with a high rate of miscarriage and premature birth [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation